The Change Agent of the Fishermen Development Area Staff of the Fisheries Development Authority of Malaysia - Yater, Luz R. (1986)
This study was conducted primarily to assess the change agent roles of the Fishermen Development Area (FDA) staff of the Fisheries Development Authority of Malaysia (LKIM). Data for this study were gathered from 59 FDA frontline officers from five selected FDAs through group self-administered questionnaires and drop-and-collect data collection method. The study revealed that majority of the respondents were 30 years old and below; majority of them completed the Cambridge Overseas School Certificate/Malaysian School Certificate; nine were Diploma and Bachelor's Degree holders and majority of them joined LKIM without any working experience. With regard to role performance of the FDA staff contacted, the study revealed that almost all of the respondents did not consider work planning as part of their responsibility; more than three-fourths consulted their state supervisors as need arises; more respondents were dissatisfied than satisfied with their job; and slightly more than three-fourths of the respondents had linkage with staff from other agencies (mainly through meetings/conferences/workshops attended). Both the assistant development officers and the development assistants found it either very difficult or not difficult at all working with the fishermen. The managers were very certain of their felt difficulties both in working with the fishermen and with colleagues/supervisors and staff from other agencies. Generally, there seemed to be lack of clear understanding of change agent's role among the respondents. Based on selected personal characteristics, the mental and experiential preparation of the staff seemed to be inadequate for the officers to carry rut their expected change agent roles. Further preparation is needed for IKIM to help its staff to be more process-oriented.